Optimizing Waqf as a Socio-Economic Financing Instrument in the Digital Era - Didih Muhamad Sudi; Akbar Sarif; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2024)
Waqf, an important Islamic philanthropic tool for social and economic financing, has a long history. However, the management and distribution of waqf often hinders wider potential benefits. Information technology can be a useful tool to overcome these various obstacles in the current digital era. The aim of this research is to identify various technologies that can be used to optimize waqf management. Specifically, this research aims to identify technologies that can be used to increase efficiency and transparency in waqf management, evaluate how the application of these technologies impacts the effectiveness of waqf management, and make strategic recommendations for waqf managers and other stakeholders. Data was collected through in-depth interviews with waqf managers, Islamic economic experts and information technology experts. In addition, annual reports of waqf institutions, government policies related to waqf, and academic literature on the digitalization of waqf management were analyzed. Thematic analysis techniques are used to find main research patterns and themes. The research results show that using digital technology in waqf management has many major advantages. Technologies such as smart contracts and blockchain can increase the security and transparency of waqf transactions, reduce the possibility of abuse, and enable more effective audits. In addition, wider waqf fundraising is made possible by digital-based crowdfunding platforms. This research finds that digital technology has great potential to optimize waqf management as a socio-economic financing tool. This technology can overcome many of the traditional problems faced by waqf management, such as lack of transparency and efficiency.